2014
DOI: 10.1074/jbc.m113.525626
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Homodimeric Triokinase/FMN Cyclase

Abstract: Mammalian triokinase, which phosphorylates exogenous dihydroxyacetone and fructose-derived glyceraldehyde, is neither molecularly identified nor firmly associated to an encoding gene. Human FMN cyclase, which splits FAD and other ribonucleoside diphosphate-X compounds to ribonucleoside monophosphate and cyclic X-phosphodiester, is identical to a DAK-encoded dihydroxyacetone kinase. This bifunctional protein was identified as triokinase. It was modeled as a homodimer of two-domain (K and L) subunits. Active cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 84 publications
(98 reference statements)
1
29
0
Order By: Relevance
“…Citrobacter DHA kinase has a known crystal structure with a unique fold [ 16 ] that defines Group 9 in the classification of kinases [ 17 , 18 ]. This enzyme, and the hTKFC model constructed by homology [ 2 ], show up a homodimer (in agreement with size exclusion chromatography data for hTKFC [ 2 ]), each subunit with two domains, K and L, linked by a long spacer ( Figure 1 ). The intertwined subunits form an elongated L2-K1-K2-L1 arrangement.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…Citrobacter DHA kinase has a known crystal structure with a unique fold [ 16 ] that defines Group 9 in the classification of kinases [ 17 , 18 ]. This enzyme, and the hTKFC model constructed by homology [ 2 ], show up a homodimer (in agreement with size exclusion chromatography data for hTKFC [ 2 ]), each subunit with two domains, K and L, linked by a long spacer ( Figure 1 ). The intertwined subunits form an elongated L2-K1-K2-L1 arrangement.…”
Section: Introductionsupporting
confidence: 80%
“…It has been suggested that K- and L-domains, connected just by a long spacer, could move with respect to each other, and that domain mobility would be required for kinase activity [10,16]. The relative mobility of both domains has been actually shown by us in a previous work with the homology model of hTKFC, where, in the course of a 75-ns trajectory of molecular dynamics, transient ATP-to-DHA approximations are seen in the L2-K1 site, displaying apparent near-attack conformations that, however, last very shortly [2].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The recent discovery of a glyceraldehyde‐phosphorylating function to a human triokinase shows the importance of this enzyme function in d ‐fructose utilization for human health and is of much interest to the molecular understanding of the Hers metabolic pathway …”
Section: Resultsmentioning
confidence: 99%